Changes in vascular pattern of chicken chorioallantois after cartilaginous extract, chondroitin sulfate and dextran sulfate treatment - Klepácek, I; Smetana, K; Stol, M (Folia biologica, 1993)
Cartilaginous extract, chondroitin sulfate C as well as dextran sulfate in gelatin pellets have an inhibitory effect on the development of fine capillaries, in contrast to pure gelatin pellets or pellets with sucrose. These results suggest an unspecific inhibitory effect of anionic saccharidic polymers on the development of chorioallantoic membrane vessels, because the chemical structure of dextran sulfate is (except anionic groups) different from chondroitin sulfate in the pure form or in the form of proteoglycans (in cartilaginous extract).
Keywords: zvířata; síran dextranu; Animals; Chondroitin Sulfates; Dextran Sulfate; gely; chondroitinsulfáty; Allantois; Gels; Chick Embryo; Proteoglycans; Gelatin; chrupavka; alantois; Cartilage; kuřecí embryo; želatina; proteoglykany